Detection and Difference Analysis of the Enzyme Activity of Colloidal Gold Nanoparticles With Negatively Charged Surfaces Prepared by Different Reducing Agents - Ma, Mingze; Cao, Junjun; Fang, Ashe; Xu, Zhihua; Zhang, Tieying; Shi, Feng (Frontiers in Chemistry, 2022)
Nanozymes are particles with diameters in the range of 1-100 nm, which has been widely studied due to their biological enzyme-like properties and stability that natural enzymes do not have. In this study, several reducing agents with different structures (catechol (Cc), hydroquinone (Hq), resorcinol (Rs),vitamin C (Vc), pyrogallic acid (Ga), sodium citrate (Sc),sodium malate (Sm),and sodium tartrate (St))were used to prepare colloidal gold with a negative charge and similar particle size by controlling the temperature and pH. The affinity analysis of the substrate H2O2 and TMB showed that the order of activities of colloidal gold Nanozymes prepared by different reducing agents was Cc, Hq, Rs, Vc, Ga, Sc, Sm, St. It was also found that the enzyme activity of colloidal gold reduced by benzene rings is higher than that of the colloidal gold enzyme reduced by linear chains. Finally, we discussed the activity of the colloidal gold peroxidase based on the number and position of isomers and functional groups; and demonstrated that the nanozymes activity is affected by the surface activity of colloidal gold, the elimination of hydroxyl radicals and the TMB binding efficiency.